2016
DOI: 10.3389/fpsyg.2016.01827
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Older Adults in a Group-Based Exercise Program Toward a Blended Intervention; A Focus-Group Study

Abstract: Ageing is associated with a decline in daily functioning and mobility. A physically active life and physical exercise can minimize the decline of daily functioning and improve the physical-, psychological- and social functioning of older adults. Despite several advantages of group-based exercise programs, older adults participating in such interventions often do not meet the frequency, intensity or duration of exercises needed to gain health benefits. An exercise program that combines the advantages of group-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 28 publications
(32 reference statements)
2
58
1
2
Order By: Relevance
“…The literature reviewed underscored the importance of having a competent exercise instructor, as older exercisers attributed great value to having an instructor who was knowledgeable about exercise, as well as about gerontology. Herein, exercise participants acknowledged the instructor's role as competent practitioner, recognizing that certification was vital toward the assurance of technical proficiency, thus ensuring some degree of safe practice (Beaudreau, 2006;Brehm, 2004;Forsyth, Handcock, Rose, & Jenkins, 2005;Mehra et al 2016;Olsen, Telenius, Engedal, & Bergland, 2015;Taylor & Pescatello, 2016;Vseteckova et al, 2018). Moreover, Oldridge (1977) argued that instructors should teach safety techniques to exercisers in order to increase exerciser self-efficacy and further reduce the likelihood of injury.…”
Section: Competencementioning
confidence: 99%
See 1 more Smart Citation
“…The literature reviewed underscored the importance of having a competent exercise instructor, as older exercisers attributed great value to having an instructor who was knowledgeable about exercise, as well as about gerontology. Herein, exercise participants acknowledged the instructor's role as competent practitioner, recognizing that certification was vital toward the assurance of technical proficiency, thus ensuring some degree of safe practice (Beaudreau, 2006;Brehm, 2004;Forsyth, Handcock, Rose, & Jenkins, 2005;Mehra et al 2016;Olsen, Telenius, Engedal, & Bergland, 2015;Taylor & Pescatello, 2016;Vseteckova et al, 2018). Moreover, Oldridge (1977) argued that instructors should teach safety techniques to exercisers in order to increase exerciser self-efficacy and further reduce the likelihood of injury.…”
Section: Competencementioning
confidence: 99%
“…The literature reviewed indicated that older adults preferred instructors who demonstrated leadership behaviors and possessed interpersonal skills, specifically the ability to understand and communicate with exercise participants; motivate and demonstrate enthusiasm; personalize instruction and show interest in the client; be patient, caring, passionate, fun, flexible, and realistic; and foster trust with clients (Beauchamp, Welch, & Hulley, 2007;Beaudreau, 2006;Bray, Gyurcsik, Culos-Reed, Dawson, & Martin, 2001;Caperchione, Mummery, & Duncan, 2011;Manson et al, 2017;McAuley & Jacobson, 1991;Mehra et al, 2016;Miyawaki et al, 2016;Olsen et al, 2015;Poole, 2001;Vseteckova et al, 2018;Wininger, 2002). Literature in this domain also demonstrated that older adults desired instructors who were organized and prepared, encouraging, understanding, in good physical shape themselves, and persuasive but also respectful of individual abilities (Costello, Kafchinshi, Vrazel, & Sullivan, 2011;Estabrooks et al, 2004;Hawley-Hague et al, 2016;Olsen et al, 2015;Vseteckova et al, 2018).…”
Section: Leaders and Communicatorsmentioning
confidence: 99%
“…Improvements are needed to engage the person deeper, especially for the interface. Motivation for regular exercise may come from a number of sources such as strengthening of a sense of self-reliance and independence, attractiveness of the human-computer interface or fear of progressive dementia 21 .…”
Section: N N O V a T I V E R E A C H D E V I C E Smentioning
confidence: 99%
“…As a result of the social aspect, motivation towards an exercise program is higher in a group setting in comparison to individual therapy in older adults [5]. However, for people with AD, it is hard to focus on the exercises for 30 minutes or longer in group due to attentional problems.…”
Section: Introductionmentioning
confidence: 99%